The importance of bank credit for the economic activity in Mexico: A manufacturing sector analysis: La importancia del crédito bancario para la actividad económica en México: Un análisis del sector manufacturero - Chavarín Rodríguez, Rubén; Tlatoa Chávez, Aurea (Universidad Autónoma de Nuevo León, 2023)
The general objective of this paper is to estimate, in Mexico’s case, the impact of commercial bank credit on economic activity in the whole manufacturing sector, and seven selected manufacturing industries. Unlike the literature that has studied the effects of bank credit in the Mexican economy, this research finds evidence (through ARDL-bounds models) of a positive and significant impact of bank credit on production for the whole sector and the following industries: i) food, ii) beverage and tobacco, iii) paper, iv) non-metallic mineral-based products, and v) transport equipment manufacturing; along with significant effects from fixed investment in machinery and equipment, and the real interest rate. In addition, we did not find evidence that loan concentration affects manufacturing production. Due to these results, this study postulates that bank credit matters as a stimulus of industrial activity, and it would be worth designing policies that strengthen and deepen such impacts. Resumen El objetivo general de este trabajo es estimar, para el caso de México, el impacto del crédito bancario sobre la actividad económica del sector manufacturero y de siete subsectores manufactureros seleccionados. A diferencia de la literatura que ha estudiado los efectos del crédito bancario en la economía mexicana, este trabajo encuentra evidencia (a través de modelos ARDL-bounds) de un impacto positivo y significativo del crédito bancario sobre la producción para el total del sector y las siguientes industrias: i) alimentos, ii) bebidas y tabaco, iii) papel, iv) productos minerales no metálicos, y v) producción de equipo de transporte; junto con efectos significativos de la inversión fija en maquinaria y equipo, y la tasa de interés real. Adicionalmente, no se halló evidencia de que la concentración del crédito afecte a la producción manufacturera. Debido a estos resultados, este trabajo postula que el crédito bancario sí importa como estímulo de la actividad industrial, y valdría la pena diseñar políticas que fortalezcan y profundicen tales impactos.